Starlikeness and Convexity of Generalized Struve Functions. (6th March 2013) - Yagmur, Nihat; Orhan, Halit
Abstract : We give sufficient conditions for the parameters of the normalized form of the generalized Struve functions to be convex and starlike in the open unit disk.